ANALISIS KELAYAKAN USAHATANI SELADA HIDROPONIK DI MASA PANDEMI COVID-19 KABUPATEN KOLAKA - Masitah, Masitah; Syahrir, Syahrir; Amin, Muhtar; Mandeva, Poresman (Jurnal AGRISEP, 2021)
Hydroponic lettuce is one type of plant that is widely developed today by farmers to be used as a farm for the community, especially for millennials. Hydroponics is a way of farming that is again up to date in the midst of the current Covid-19 pandemic because it is not difficult to cultivate and can provide benefits for farmers.  The purpose of the research was to determine the feasibility of hydroponic lettuce farming during the Covid-19 pandemic. The research was conducted in Kolaka Regency with a population of 19 hydroponic lettuce farmers. Business analysis that will be used in this study is income analysis (?), Business Ratio (R/C), Payback Period (PBP) and Break Even Point (BEP).  The research was conducted in Kolaka Regency with a population of 19 hydroponic lettuce farmers. The results of the analysis of the feasibility of hydroponic lettuce farming during the Covid-19 pandemic are known to be profitable because the value of R/C>1 of 3.43 this indicates that the farm is profitable with the average income of hydroponic lettuce farming businesses already above the Kolaka District UMK of Rp. 2,502,500, from the results of the analysis PBP obtained a figure of 0.3 years to return the investment of mangrove crab business takes about 3.6 months and to reach the break-even point (BEP) obtained a minimum gross receipt of Rp. 840,349.3 this means that the hydroponic lettuce farming during the Covid-19 pandemic is worth trying.